The Transformation of Tafsir Bi Al-Ra'yi: History, Methodological Limitations, and the Dynamics of Scholarly Debate - Muhammad Bayu Fitriansyah; Saptanadi Yudistira; Eni Zulaiha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to discuss the transformation of Tafsir bi al-ra’yi: its history, methodological boundaries, and the dynamics of scholarly debates. The research employs a qualitative approach using a descriptive-analytical method. Tafsir bi al-ra’yi is an interpretative method of the Qur’an based on ijtihad, which emerged in the 3rd century Hijri, particularly during the Abbasid era, to address the demands of the times. This method must be carried out by knowledgeable interpreters adhering to the principles of tafsir to ensure alignment with the Qur’an, Sunnah, and ijma’ of the scholars. While it allows intellectual freedom, it remains constrained to avoid subjective desires. Scholars have differing views: some support it as a necessary form of ijtihad, while others reject it due to concerns about conflicting with definitive texts (nash qath’i). This study concludes that Tafsir bi al-ra’yi plays a significant role in enriching the understanding of the Qur’an but emphasizes that its application must balance methodological caution and respect for the authority of the Qur’anic text.